Fabrication of polycaprolactone/calcium phosphates hybrid scaffolds impregnated with plant extracts using 3D printing for potential bone regeneration (2023)
The increase in critical bone diseases and defects in the world’s population increases the need for bone substitutes to restore form and function. Organic and inorganic scaffolds with antibacterial properties could provide advantages for bone regeneration. In this study, we obtained scaffolds of polycaprolactone (PCL) charged with calcium phosphates nanoparticles and impregnated with extracts of Colombian plants as an alternative for potential bone regeneration. Calcium phosphate nanoparticles were obtained via auto-combustion synthesis. The nanoparticles were incorporated into the PCL with a chemical dissolution-disperse process. The composite obtained was used to produce a filament to print Triply Periodic Minimal Surface (TPMS) based scaffolds. Such geometry facilitates cellular growth thanks to its interconnected porosity. The scaffolds were impregnated with extracts of Justicia cf colorifera (Acanthaceae), and Billia rosea (Sapindaceae) due to their ancestral medical applications. A physical and biological characterization was conducted. The process to print scaffolds with an enhanced geometry to facilitate the flux of biological fluids was successful. The scaffolds loaded with B. rosea showed strong antibacterial behavior, suggesting the presence of reported terpenoids with antibacterial properties. The approach used in this study evidenced promising prospects for bone defect repair.